Indicators of soil quality in the implantation of no-till system with winter crops - Nogueira, Marco; Telles, Tiago; Fagotti, Dáfila; Brito, Osmar; Prete, Cássio Egídio; Guimarães, Maria (Revista Ciência Agronômica, 2014)
We assessed the effect of different winter crops on indicators of soil quality related to C and N cycling and C fractions in a Rhodic Kandiudult under no-till system at implantation, during two growing seasons, in Londrina PR Brazil. The experimental design was randomized blocks with split-plot in time arrangement, with four replications. The parcels were the winter crops: multicropping of cover crops with black oat (Avena strigosa), hairy vetch (Vicia villosa) and fodder radish (Raphanus sativus); sunflower (Heliantus annuus) intercropped with Urochloa ruziziensis; corn (Zea mays) intercropped with Urochloa; and corn; fodder radish; or wheat (Triticum aestivum) as sole crops. The subplots were the years: 2008 and 2009. Determinations consisted of total organic C, labile and resistant C, total N, microbial biomass C and N, the C/N ratio of soil organic matter, and the microbial quotient (qMic), besides microbiological and biochemical attributes, assessed only in 2009. The attributes significantly changed with the winter crops, especially the multicropping of cover crops and fodder radish, as well as effect of years. Despite stimulating the microbiological/biochemical activity, fodder radish cropping decreased the soil C in the second year, likewise the wheat cropping. The multicropping of cover crops in winter is an option for management in the establishment of no-till system, which contributes to increase the concentrations of C and stimulate the soil microbiological/biochemical activity.